2014
DOI: 10.1007/s00590-014-1528-7
|View full text |Cite
|
Sign up to set email alerts
|

High-energy tibial plateau fractures: external fixation versus plate fixation

Abstract: Although lack of good quality randomized control trials, there are rather enough samples supporting the current available results. Meanwhile, future multicentered, randomized, controlled studies should be implemented to test these outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
12
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 30 publications
8
12
0
1
Order By: Relevance
“…In agreement with our data regarding earlier healing following internal stabilization, Krupp et al described a decreased time to union after plate fixation of bicondylar tibia fractures reporting an average of 5.9 months compared to 7.4 months for external fixation [ 13 ]. Although a recent meta-analysis comparing both treatment methods for tibial plateau fractures found no significant difference regarding the time to union [ 7 ], the recorded data document a similar tendency (17.73 ± 4.87 after external fixation vs 15.64 ± 4.36 weeks following plate fixation). This study included 22 case series and a retrospective cohort study, indicating the lack of direct comparing trials and a low summary evidence level.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In agreement with our data regarding earlier healing following internal stabilization, Krupp et al described a decreased time to union after plate fixation of bicondylar tibia fractures reporting an average of 5.9 months compared to 7.4 months for external fixation [ 13 ]. Although a recent meta-analysis comparing both treatment methods for tibial plateau fractures found no significant difference regarding the time to union [ 7 ], the recorded data document a similar tendency (17.73 ± 4.87 after external fixation vs 15.64 ± 4.36 weeks following plate fixation). This study included 22 case series and a retrospective cohort study, indicating the lack of direct comparing trials and a low summary evidence level.…”
Section: Discussionmentioning
confidence: 86%
“…Clinical results were reported for both treatment standards [ 5 , 6 ]; however, comparison of studies are lacking. Recently, a systematic review evaluated both principals based on the published cohort studies [ 7 ]. Although the article makes a differentiated analysis available, there are obvious difficulties.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, with the intention to imitate the anatomical reduction of the medial tibial plateau fracture, no displacement between the fractured segments was created, which made the model the same as a simple non-displaced fracture. However, it should be noted that multiple pinning under the guidance of an image intensifier was clinically preferred to buttress plate fixation for the treatment of non-displaced tibial plateau fractures [ 22 , 23 ]. In contrast, displaced fractures of the medial plateau (Schatzker type IV) often are quite unstable and are generally best treated with open reduction and internal fixation with a medial buttress plate [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…10 ). Comparing this with double-plate internal fixation, some studies have reported a lower rate of deep infections [ 60 , 61 ], but a slight increase in superficial infections [ 60 , 62 ], partly due to the poor initial condition of the tissues, together with an increased incidence of malunion and of traumatic arthritis [ 63 ].…”
Section: Treatmentmentioning
confidence: 99%
“…found that fractures treated with a hybrid external fixator more commonly present traumatic arthritis, while those treated with internal fixation plates more often have valgus deformity. Nevertheless, these authors stress the need to conduct larger-scale studies to confirm their results [ 63 ]. The minimally-invasive use of a single plate reduces the incidence of infection and nonunion, because the periosteum is retained intact.…”
Section: Treatmentmentioning
confidence: 99%